A Rare Case of Dysferlinopathy in an Adolescent from a Resource-Limited Setting - Shrestha, Priya; Chaudhary , Chandan; Thapa, Lekhjung; Bhattarai, Suman (Nepal Journal of Neuroscience, 2025)
Dysferlinopathies are rare autosomal recessive muscular disorders with varying phenotypes, including Miyoshi Myopathy (MM) and Limb-Girdle Muscular Dystrophy type 2B (LGMD2B). They result from mutations in the DYSF gene, which encodes dysferlin, a protein crucial for sarcolemmal repair. Diagnosis can be challenging due to clinical variability, necessitating genetic testing. We present the case of an 18-year-old girl with progressive lower limb weakness and elevated creatine kinase levels, who was ultimately diagnosed through genetic analysis. This case emphasizes the importance of genetic testing for accurate diagnosis, improved patient care, and appropriate genetic counseling.